Convergent Digital Infrastructures and the Role of (Net-)Neutrality - Joachim Sedlmeir; Stefan Hopf; Rahild Neuburger; Arnold Picot (International Telecommunications Society (ITS), 2017)
The integration of modern information and communication technologies (ICT) triggers an evolutionary process from previous analog towards convergent digital infrastructures that are the basis for new, cross-domain services and applications. The implementation, however, poses new requirements and regulatory challenges. Among these, a broader view on net neutrality appears to be a crucial precondition that exceeds the single focus on the non-discriminatory transmission of data via the proprietary telecommunication infrastructures of different network operators as critical gatekeepers. Rather, a new, systemic way of thinking in digital infrastructures is necessary. Hereby, the scope of neutrality expands to different functions on several levels of interconnected infrastructures in order to design interoperable systems as platforms for futureorientated, cross-domain services. To adequately describe and comprehend the trajectory from previous analog to convergent digital infrastructures that allow novel services via specific platforms and facilitate an interaction across various domains and industries, we introduce and illustrate distinctive evolutionary steps that reflect different levels of convergence. Since the complex interrelationships and interdependencies within convergent digital infrastructures cannot be readily analyzed in a holistic manner, this paper focuses on the mobility domain as primarily field of analysis. For the examination of digital mobility infrastructures in the context of neutrality, a case study-orientated approach has been developed that divides the field of analysis into three predefined levels and allows an investigation of the specific requirements to implement such convergent infrastructures from a technology-, data- and service-specific perspective. Based on this analysis, we define distinctive extensions to the existing view on net neutrality and, thereby, contribute to the already existing claims in academic literature for the conception of a more holistic view on this topic.
Keywords: 330; Digital Infrastructures; (Net-)Neutrality; Convergence; Digital Mobility Services